Rykantai Church of the Saint Trinity, postcard, 1930 - Jan Bulhak (Wikimedia Commons, 1930)
Notice image issue de Wikimedia Commons. Titre: Rykantai Church of the Saint Trinity, postcard, 1930. Rykantai Church of the Saint Trinity, postcard, 1930
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; architecture; Histoire Locale; église; Carte postale